Effects Of Testing Temperature On Fracture Mode Of Unidirectional Cfrp tension specimen - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The previous study shows that unidirectional CM' tensile specimen that necked on the center fractures in three modes. namely tension mode, shear mode and combination mode, depends on the thickness ratio of the specimen, This difference in fracture mode occurs due to the change in relationship between shear fracture strength and tension fracture strength. In this study, these fracture strength relationships were diseased further to understand the effect Qt- the change in material properties on fracture modes by varying testing temperature. It is clear from this study that the lower the testing temperature, the transition polio between shear fracture mode and tension fracture mode moves to the higher value of thickness ratio, This evident is claryied by the fact that the decreasing testing temperature causing the increase in interlaminr shear strength of the specimen.